Multi-purpose (MPs) chair / Nur Huda Husna Mohd Hasmy … [et al.] - Mohd Hasmy, Nur Huda Husna; Yaacob, Zalini; Mohd Zaidi, Rusydiana; Borhanordin, Amirah Hazimah; Kamaludin, Nur Aqila Nadira; Anuar, Fatin Syazana; Md Taib, Norraeffa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Multi-purpose (MPs) Chair is a chair that has been modified from existing product which is more convenient and friendly user. This MPs Chair is made for both right and left-handed users, so that they will feel comfortable while using the MPs Chair. It is made of fiber wood that is known as environmentally friendly products. As have been stated previously, the main advantage is to provide comfort especially to the left-handed users as the existing products usually focus for the right-handed users. In addition, it also has an external slot that can be pulled out which have a flip-off bookstand. Not only that, the MPs Chair also has hooks attached at the back of the chair with a limit of 3 kg weight. The impact can be described as it will provide fairness to all users and it will cause less harm to the environment. This product also can help certain organization to cut their cost by only buying the MPs chair, instead of they need to buy the tables and chairs separately. This will actually cause double spending. Other than that, this multi-purpose chair also has cushion that will provide comfort for the users' backbones. We highly recommend this MPs Chair for the educational sector.